(untitled) (Journal of the College of Education for Women, 2019)
AbstractThe curriculum is the major effective tool in achieving the goals ofeducation and society. Many countries that want to reach the forefront of developed countriesthrough their curriculum have realized this fact. School text book, theapplication assessment for knowing the rang of success or fail of this textbook in achieving the general aims. therefore this study aims at assessing theprincipals and techniques of geography text book for fourth secondary class ofliterary studying from the teachers point of view according to the fields of thebook, style of material, technical arrangement of the material, ethnicalarrangement the language of the book, style of the material, technicalarrangement of the activities of the language of the book .The researcher has used questionnaire for fulfilling the research aims.The study is designed according to the pilot study in which its validity andreliability have been examined.The study contains ( 50 ) items have divided in to (5 ) fields .The researcher has used the mean. Pearson’s correlation coefficient andpercentage as a statistical means.The results show that the book divesting has got the first rank in 80 .14% andin mean 2.40, the language of the mean (6.12%) and mean (1.83) and at thefinal rank is the book activities which have got ( 58.22% ) and mean ( 1.69 )In the light of the finding of the present study, several conclusion,recommendation and suggestions for further study have been made .